Pemanfatan Digital Marketing Di UMKM Kampoeng Jadoel Melalui Media Sosial - Ahmad Ashifuddin Aqham; Laksamana Rajendra H.A.F; Haris Ihsanil Huda; Bagus Sudirman; Moh Muthohir (jurnal ABDIMAS Indonesia, 2024)
UMKM have an important role in the Indonesian economy, but the biggest challenge they face is limited marketing and consumer reach. This research aims to analyze the use of digital marketing through social media as a marketing strategy in Kampoeng Jadoel UMKM . The research method used is descriptive qualitative with data collection techniques in the form of observation, interviews and literature study. The research results show that the use of social media such as Instagram, Facebook and WhatsApp can significantly increase brand awareness and market reach of Kampoeng Jadoel UMKM . Through interesting content and active interaction strategies with customers, UMKM are able to increase sales and consumer loyalty. Digital marketing has proven to be an effective, efficient and affordable solution for MSMEs in developing their business in the digital era.